Dimension-Dependent Bandgap Narrowing and Metallization in Lead-Free Halide Perovskite Cs3Bi2X9 (X = I, Br, and Cl) under High Pressure - Guangbiao Xiang; Yanwen Wu; Man Zhang; Chen Cheng; Jiancai Leng; Hong Ma (Nanomaterials, 2021)
Low-toxicity, air-stable cesium bismuth iodide Cs3Bi2X9 (X = I, Br, and Cl) perovskites are gaining substantial attention owing to their excellent potential in photoelectric and photovoltaic applications. In this work, the lattice constants, band structures, density of states, and optical properties of the Cs3Bi2X9 under high pressure perovskites are theoretically studied using the density functional theory. The calculated results show that the changes in the bandgap of the zero-dimensional Cs3Bi2I9, one-dimensional Cs3Bi2Cl9, and two-dimensional Cs3Bi2Br9 perovskites are 3.05, 1.95, and 2.39 eV under a pressure change from 0 to 40 GPa, respectively. Furthermore, it was found that the optimal bandgaps of the Shockley–Queisser theory for the Cs3Bi2I9, Cs3Bi2Br9, and Cs3Bi2Cl9 perovskites can be reached at 2–3, 21–26, and 25–29 GPa, respectively. The Cs3Bi2I9 perovskite was found to transform from a semiconductor into a metal at a pressure of 17.3 GPa. The lattice constants, unit-cell volume, and bandgaps of the Cs3Bi2X9 perovskites exhibit a strong dependence on dimension. Additionally, the Cs3Bi2X9 perovskites have large absorption coefficients in the visible region, and their absorption coefficients undergo a redshift with increasing pressure. The theoretical calculation results obtained in this work strengthen the fundamental understanding of the structures and bandgaps of Cs3Bi2X9 perovskites at high pressures, providing a theoretical support for the design of materials under high pressure.